RACISM IN ROBERT TOWNE’S ASK THE DUST MOVIE (2006): A SOCIOLOGICAL APPROACH - Minarti, Sri (2010)

(untitled)
This research paper elaborates the difficulty faced by immigrant in Great Depression Era in Los Angeles, which analyzed through sociological approach. The objectives of the research, are to analyze the movie based on its structural elements and to analyze the movie based on its structural elements and to analyze the movie based on the sociological approach, by identifying the relation between the movie and the social background of the early twentieth first century American society. This research paper belongs to a qualitative research. The sources of the data come from both primary data source, which is Ask the Dust movie and secondary data sources are information about the author’s biography, websites about the movie, the social background of American society in the early twentieth first century and theory of sociological. The method to analyze the data is descriptive analysis. Having analyzed the movie, the researcher comes to the conclusion as follows: Firstly, based on the structural analysis, it is evident that in Ask the Dust movie, Robert Towne wants to convey a moral message that racism is not appropriate with humanity. Secondly, based on the sociological analysis, it is clear that there is a close relation between the production of this movie and the social reality underlying it. The major factors that contribute to the production of the movie among others are the global issues of racism in Great Depression Era in 1932.